IMPROVING CHILDREN’S WRITING SKILLS THROUGH THE SHARED-WRITING PROGRAM AT UPT SDN 253 GRESIK - Eka Oktavia Ramadhina; Amelasasih, Prianggi (World Psychology, 2025)
Writing proficiency is a fundamental literacy skill that supports children’s cognitive, emotional, and academic development, yet many early-grade students continue to face difficulties in symbol recognition, fine-motor coordination, and idea organization. These challenges require effective instructional interventions that promote gradual and supported learning. This study aims to examine the effectiveness of a shared-writing program in improving the writing skills of first-grade students at UPT SDN 253 Gresik. A qualitative descriptive approach was employed, integrating classroom observation, documentation, and pre–post assessment using standardized writing indicators. The intervention consisted of structured shared-writing sessions in which the teacher modeled writing processes while students contributed ideas and practiced reproducing letters and simple words. Findings indicate a substantial improvement in the participant’s writing performance, demonstrated by an increase from 66% (Developing as Expected) during the pre-test to 100% (Very Well Developed) in the post-test. Students showed notable gains in symbol recognition, meaningful scribbling, and accurate imitation of written forms. The shared-writing approach also enhanced motivation, confidence, and participation. The study concludes that shared-writing is an effective collaborative strategy for strengthening foundational writing skills in early elementary learners and can be recommended as a supportive intervention for students with early writing difficulties.